15-Deoxy-Δ12, 14-prostaglandin J2 Exerts Antioxidant Effects While Exacerbating Inflammation in Mice Subjected to Ureteral Obstruction. (19th April 2017) - Nilsson, Line; Palm, Fredrik; Nørregaard, Rikke
Abstract : Urinary obstruction is associated with inflammation and oxidative stress, leading to renal dysfunction. Previous studies have shown that 15-deoxy-Δ 12, 14 -prostaglandin J2 (15d-PGJ2 ) has both antioxidant and anti-inflammatory effects. Using a unilateral ureteral obstruction (UUO) mouse model, we examined the effects of 15d-PGJ2 on oxidative stress and inflammation in the kidney. Mice were subjected to UUO for 3 days and treated with 15d-PGJ2 . Protein and RNA expression were examined using immunoblotting and qPCR. 15d-PGJ2 increased NF-E2-related nuclear factor erythroid-2 (Nrf2) protein expression in response to UUO, and heme oxygenase 1 (HO-1), a downstream target of Nrf2, was induced by 15d-PGJ2 . Additionally, 15d-PGJ2 prevented protein carbonylation, a UUO-induced oxidative stress marker. Inflammation, measured by nuclear NF- κ B, F4/80, and MCP-1, was increased in response to UUO and further increased by 15d-PGJ2 . Renal injury was aggravated by 15d-PGJ2 treatment as measured by kidney injury molecule-1 (KIM-1) and cortical caspase 3 content. No effect of 15d-PGJ2 was observed on renal function in mice subjected to UUO. This study illustrates differentiated functioning of 15d-PGJ2 on inflammation and oxidative stress in response to obstructive nephropathy. High concentrations of 15d-PGJ2 protects against oxidative stress during 3-day UUO in mice; however, it aggravates the associated inflammation.